Building the State Through Stick Blows. Garavaglia, the Fiscal-Military State and the Social History of War - Rabinovich, Alejandro M. (2019)
The academic production of Dr. Juan Carlos Garavaglia was prolific, for this reason, his valuable contributions to the Latin American historiography have conformed a wide spectrum in which studies of agrarian and rural history in different countries of this region stand out, as well as state construction on the continent; research work in which the issue of the militia and war is revealed in a relevant and frequent way. This article outlines the scholarly path of Dr. Garavaglia: those who paid for his training, his main writings and the lines of research that he left open after his death.